CRAFTING MARKETABLE GRADUATES: A CASE STUDY ON CRAFTING MARKETABLE GRADUATES: A CASE STUDY ON ENHANCING EMPLOYABILITY AT THE NATIONAL UNIVERSITY OF LESOTHOENHANCING EMPLOYABILITY AT THE NATIONAL UNIVERSITY OF LESOTHO - Makolo, Thetsane Moloko; Mbaeso , Motselisi ’05; Makhetha, Lesotho T (International Journal of Allied Research in Marketing and Management (IJARMM), 2024)
In the contemporary landscape of global competition and rapidly evolving technology and economies, the pervasive challenge of graduate unemployment looms large across nations, posing a critical issue for policy-makers and educators alike (Keech, 2006). This quandary is further compounded by a surge in the number of unemployed graduates emerging from Higher Education Institutions (HEI) (Rok, 2013). The prevalence of unemployment among university graduates is not solely a consequence of job scarcity; rather, it is exacerbated by the scarcity of candidates equipped with the requisite employable skills sought by employers (Emeh, Nwanguma, & Abaroh, 2012; Pitan, 2016; Judd et al., 2015).This abstract delves into the multifaceted dimensions of the global challenge of graduate unemployment, with a particular focus on the Higher Education landscape. Drawing on empirical evidence, the narrative explores the gravity of the situation, exemplified by statistics from Lesotho, where an estimated 7,500 graduates annually enter the labor market, with half facing unemployment challenges, and 19% of them originating from HEIs (Central Bank, 2012; Khaola, 2010). This stark reality underscores a pressing need to dissect the root causes, with an emphasis on the role of skills, or the lack thereof, in hindering graduates’ employability. The analysis contends that the traditional paradigm of education is confronted with a transformative imperative. It posits that merely possessing a degree is no longer a sufficient marker of employability, and the emphasis must shift towards cultivating a skill set aligned with the dynamic demands of the job market. Insights from various studies, including those conducted in Lesotho, suggest that a substantial proportion of graduates grapple with unemployment due to a deficiency in essential employability skills (Emeh et al., 2012). In addressing this global conundrum, the abstract explores potential avenues for reform in Higher Education, advocating for a paradigm shift towards a more skills-centric approach. It emphasizes the need for a collaborative effort between educational institutions and industries to bridge the existing gap and ensure that graduates are adequately equipped to meet the demands of the contemporary job market